Słownictwo angielskie w Nowym słowniku poprawnej polszczyzny - Włodarczyk, Anna (Acta Universitatis Lodziensis. Folia Linguistica, 2002)
The aim of the article was to describe about 680 English loanwords found in new Polish dictionary describing contemporary language by A. Markowski (1999). In Nowy słownik poprawnej polszczyzny there are approximately 300 completely new English loanwords in comparison with the earlier dictionaries of this type. Each lexical entry consists of the headword, its graphic variants, phonetic transcription if it difters from spelling and detailed grammar comment. There are also lots of examples showing changes in meaning and contexts o f using the described vocabulary. Such semantic fields as „economy”, „food ”, „clothing”,„ sport”, „music”, „technology”, „entertainment” seem to include the biggest number of loanwords, which are easily adapted into Polish. In the dictionary each Pole can find strong advice not to overuse the English loanwords in Polish language.